2003
DOI: 10.1046/j.1432-1033.2003.03856.x
|View full text |Cite
|
Sign up to set email alerts
|

A differential scanning calorimetry study of tetracycline repressor

Abstract: Tetracycline repressor (TetR), which constitutes the most common mechanism of bacterial resistance to an antibiotic, is a homodimeric protein composed of two identical subunits, each of which contains a domain possessing a helixturn-helix motif and a domain responsible for binding tetracycline. Binding of tetracycline in the protein pocket is accompanied by conformational changes in TetR, which abolish the specific interaction between the protein and DNA. Differential scanning calorimetry (DSC) and CD measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
(60 reference statements)
3
9
0
Order By: Relevance
“…19,20,27 This is reflected by an increase in the midpoint of the denaturant concentration from 3.2 M to 4.8 M urea (Fig. S5) and by an increase in T m from 58°C to 71.0°C upon addition of ATc to TetR (Reichheld et al, 20 Kedracka-Krok and Wasylewski, 27 and this study). In order to investigate whether peptide binding leads to a similar stabilization of TetR, we performed urea-induced denaturation experiments monitored by CD spectroscopy (Fig.…”
Section: Tip and Tap Binding Repositions Loop L6-l7supporting
confidence: 57%
“…19,20,27 This is reflected by an increase in the midpoint of the denaturant concentration from 3.2 M to 4.8 M urea (Fig. S5) and by an increase in T m from 58°C to 71.0°C upon addition of ATc to TetR (Reichheld et al, 20 Kedracka-Krok and Wasylewski, 27 and this study). In order to investigate whether peptide binding leads to a similar stabilization of TetR, we performed urea-induced denaturation experiments monitored by CD spectroscopy (Fig.…”
Section: Tip and Tap Binding Repositions Loop L6-l7supporting
confidence: 57%
“…A number of transcriptional regulators consisting of an effector binding domain and a DNA binding domain have been described previously, i.e., TetR (2) and the NmrA regulator (16), to cite some, and have been analyzed by DSC. These studies showed that these proteins unfold in a single event, pointing toward the cooperative unfolding of both domains (14,16). In contrast, PtxS domains seem to unfold independently, as suggested by our DSC studies shown in Fig.…”
supporting
confidence: 60%
“…DSC studies of other proteins have revealed in a number of cases that cooperative domain unfolding reflects functional interdomain cross-talk (57)(58)(59). Data thus suggest functional interdomain interaction in CheR.…”
Section: Discussionmentioning
confidence: 99%